2023
DOI: 10.1021/acscentsci.2c01336
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytic Synthesis of White Phosphorus Is Promoted in Oxide-Deficient Molten Salts

Abstract: Elemental white phosphorus (P 4 ) is a key feedstock for the entire phosphorus-derived chemicals industry, spanning everything from herbicides to food additives. The electrochemical reduction of phosphate salts could enable the sustainable production of P 4 ; however, such electrosynthesis requires the cleavage of strong, inert P−O bonds. By analogy to the promotion of bond activation in aqueous electrolytes with high proton activity (Brønsted−Lowry acidity), we show that low oxide anion activity (Lux−Flood ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…License: CC BY-NC-ND 4.0 114 available iron oxides, leading to the formation of ferrophosphorus and low to moderate P4 yields. 53,54 • Electrolysis of phosphate rock in calcium chloride 55 or in a sodium metaphosphate melt 56 has been proposed. These processes hold promise for reducing the energy use of P4 production (typically by 25-30% in theory) but need thorough development.…”
Section: New Developments In Phosphorus Chemistrymentioning
confidence: 99%
“…License: CC BY-NC-ND 4.0 114 available iron oxides, leading to the formation of ferrophosphorus and low to moderate P4 yields. 53,54 • Electrolysis of phosphate rock in calcium chloride 55 or in a sodium metaphosphate melt 56 has been proposed. These processes hold promise for reducing the energy use of P4 production (typically by 25-30% in theory) but need thorough development.…”
Section: New Developments In Phosphorus Chemistrymentioning
confidence: 99%
“…For example, the electrochemical reduction of phosphate salts enables the sustainable production of elemental white phosphorus (P 4 ); however, this requires the cleavage of strong and inert P–O bonds. Surendranath and his colleagues have shown that the low oxide anion activity, characterized by Lux-Flood acidity, effectively promotes the activation of P–O bonds in molten sodium trimetaphosphate . The Lux acidic phosphoryl anhydride linkages play a crucial role in facilitating the selective and efficient electrosynthesis of P 4 , achieving an impressive 95% Faradaic efficiency.…”
Section: Electrochemical Conversion Beyond Electrocatalystsmentioning
confidence: 99%
“…License: CC BY-NC-ND 4.0 available iron oxides, leading to the formation of ferrophosphorus and low to moderate P4 yields. 53,54  Electrolysis of phosphate rock in calcium chloride 55 or in a sodium metaphosphate melt 56 has been proposed. These processes hold promise for reducing the energy use of P4 production (typically by 25-30% in theory) but need thorough development.…”
Section: Phosphorus Sustainabilitymentioning
confidence: 99%